Peri-operative management of Antithrombotic agents: Results of the 3rd Consensus Meeting of the Portuguese Society of Anesthesiology - Fonseca, Cristiana; Alves, Joana; Araújo, Fernando (Journal of the Portuguese Society of Anesthesiology, 2014)
The perioperative management of patients chronically medicated with anticoagulants and antiplatelet agents is a clinical problem, but also a challenge for all specialties dealing with the patient in the perioperative period. The recommendations of the various scientific societies with different levels of evidence and review of articles provide indications of their approach. However, the lack of evidence from randomized controlled studies in this area determines that many of the recommendations and guidelines are the result of multidisciplinary meetings, where the literature and experience of the clinical centers are determining factors for the development strategies in the peri-operative management for these patients. Thus, this consensus meeting, involving national an consenso 2014 d international experts from various specialties including Anesthesiology, Imunohemoterapy, Cardiology, Internal Medicine, General Surgery, Vascular and Cardiothoracic Surgery aimed to develop recommendations for the perioperative management of the patient receiving anticoagulants and antiplatelets agents. With the direct introduction of oral anticoagulants in clinical practice, new issues have been evaluated. Although they are drugs with predictable pharmacokinetics, lack of experience and data in the literature interfere in the perioperative management of these patients. Determine the balance between thromboembolic risk factors associated with patients and the risk of bleeding associated with the surgical procedure is fundamental. It is intended disclose the time of suspension that dictate the perioperative period, the need of bridging with short time drugs and the laboratory monitoring in case of bleeding. This meeting also addressed other anticoagulants and antiplatelet agents in perioperative and hemorrhagic context.